2014
DOI: 10.1111/1365-2435.12283
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to low‐dose radiation atChernobyl favours adaptation to oxidative stress in birds

Abstract: Summary 1.Ionizing radiation produces oxidative stress, but organisms can adapt to their exposure with physiological adaptive responses. However, the role of radioadaptive responses in wild populations remains poorly known. 2. At Chernobyl, studies of birds and other taxa including humans show that chronic exposure to radiation depletes antioxidants and increases oxidative damage. Here, we present analyses of levels of the most important intracellular antioxidant (i.e. glutathione, GSH), its redox status, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 96 publications
(176 reference statements)
3
104
0
Order By: Relevance
“…Moreover, ATM can be activated by oxidative stress independently from DBS-related activation by the MRN complex (Guo et al, 2010). Antioxidant production likely constitutes a major part of the adaptive response against environmental radioactivity in birds within and around the CEZ (Galván et al, 2014) and in cell lines of fibroblasts from bank voles (Mustonen et al, submitted). Moreover, a change in fur color of bank voles within the CEZ was attributed to downregulation of pheomelanin to reallocate antioxidants to ROS defense (Boratynski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ATM can be activated by oxidative stress independently from DBS-related activation by the MRN complex (Guo et al, 2010). Antioxidant production likely constitutes a major part of the adaptive response against environmental radioactivity in birds within and around the CEZ (Galván et al, 2014) and in cell lines of fibroblasts from bank voles (Mustonen et al, submitted). Moreover, a change in fur color of bank voles within the CEZ was attributed to downregulation of pheomelanin to reallocate antioxidants to ROS defense (Boratynski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is very little information on the wildlife in the contaminated area of Abukuma Mountains before the F1NPP accident. It will be desirable to monitor the ecosystem and several principal wildlife species, such as some of the dominant 10 birds (explained previously), S. scrofa and unique primate Macaca fuscata (Hayama et al 2013), until most of the ecosystems and human societies regain stability in five or more decades later (Galvan et al 2014).…”
Section: Environmental Factors That Affect Wildlifementioning
confidence: 99%
“…This ROS production, however, is reduced in the benzothiazole moiety as compared to the benzothiazine moiety due to the rather stable nature of the former (Wakamatsu et al 2009). Hence, pheomelanins with higher relative contents of benzothiazoles are less prooxidant under radiation exposure (Galván et al 2014 and cited references). The analysis of benzothiazine/ benzothiazole ratios in different biological tissues gives information about the color phenotypes generated by the different pheomelanin moieties.…”
Section: Differential Costs Of Pheomelanin Formsmentioning
confidence: 99%
“…Regarding pheomelanins, there is increasing evidence that pheomelanin production represents a cost under environmental conditions or physiological processes that require a high level of protection against ROS production, and it has recently been shown that a shift toward the production of pheomelanins with a higher benzothiazole/benzothiazine ratio facilitates the acclimation of birds to relatively high exposure to ionizing radiation, which produces oxidative stress (Galván et al 2014). Pheomelanin-based colors confer camouflage or concealment and act as signals of individual quality, but certainly not all pheomelanin-based color traits are involved in concealment or signaling.…”
Section: Evolutionary Implications Of Heterogeneity In Melanin Chemistrymentioning
confidence: 99%
See 1 more Smart Citation